2011
DOI: 10.1017/s1360674311000013
|View full text |Cite
|
Sign up to set email alerts
|

An open-sesame approach to English noun phrases: defining the NP (with an introduction to the special issue)

Abstract: The category of the noun phrase in English has received much attention in the literature. This article discusses the main defining features of the category from different theoretical angles. Issues such as its structural status, the determination and characterisation of its (morphosyntactic, semantic, cognitive) head, the structural slots which are available in the phrase, and the different possibilities as far as word order is concerned will be approached from structural, syntactic, functional and cognitive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Undoubtedly understood as a call to action, the research situation has since improved in favour of the English noun phrase, which is reflected in a number of monographs devoted to understanding structure, variation and diachronic change of the English NP from a range of different perspectives (see, e.g., Meyer 2000; Keizer 2007; Berlage 2014). This assessment is confirmed by Martínez-Insua & Pérez-Guerra (2011) in their introduction to a special issue on noun phrase structure in English, where it is reported that ‘[s]tudies on noun phrases abound in the linguistics literature, and come from a variety of different perspectives and theoretical backgrounds’ (Martínez-Insua & Pérez-Guerra 2011: 201). In particular, the relevance of the English NP in the context of linguistic complexity has been increasingly acknowledged in research from variationist (Brunner 2014; Schilk & Schaub 2016), register (Biber & Gray 2011) and second-language perspectives (Biber, Gray & Ponpoon 2011; Parkinson & Musgrave 2014; Kreyer & Schaub 2018).…”
mentioning
confidence: 59%
“…Undoubtedly understood as a call to action, the research situation has since improved in favour of the English noun phrase, which is reflected in a number of monographs devoted to understanding structure, variation and diachronic change of the English NP from a range of different perspectives (see, e.g., Meyer 2000; Keizer 2007; Berlage 2014). This assessment is confirmed by Martínez-Insua & Pérez-Guerra (2011) in their introduction to a special issue on noun phrase structure in English, where it is reported that ‘[s]tudies on noun phrases abound in the linguistics literature, and come from a variety of different perspectives and theoretical backgrounds’ (Martínez-Insua & Pérez-Guerra 2011: 201). In particular, the relevance of the English NP in the context of linguistic complexity has been increasingly acknowledged in research from variationist (Brunner 2014; Schilk & Schaub 2016), register (Biber & Gray 2011) and second-language perspectives (Biber, Gray & Ponpoon 2011; Parkinson & Musgrave 2014; Kreyer & Schaub 2018).…”
mentioning
confidence: 59%
“…In this way, the researcher suggested that "A person with L1 Urdu language must avoid the translation techniques for mastering in the English language as L2 because it may lead to a wrong syntactic and grammatical sentence structure". (Insua & Guerra, 2011) Syntax Complexities Kiani (2011) conducted a study on the examination of predicate complexity and syntax of the Urdu Language. Primarily, the major concern focuses on the main and light verb functionality in a clause that is studied under the "Minimalist" key concept of (Chomsky, A Minimalist Program for Linguistic Theory, 1993) from personal observations and a collection of books.…”
Section: Linguistics Experimentation and Observationsmentioning
confidence: 99%
“…As far as the rules of Government and Binding theory are concerned, they are already set out as a paradigm for sentences that a researcher going to analyze with the reference of a noun phrase and the determiner. (Insua & Guerra, 2011)…”
Section: Significance Of Noun Phrasementioning
confidence: 99%